2021
DOI: 10.1038/s41467-021-22773-1
|View full text |Cite
|
Sign up to set email alerts
|

A unified route for flavivirus structures uncovers essential pocket factors conserved across pathogenic viruses

Abstract: The epidemic emergence of relatively rare and geographically isolated flaviviruses adds to the ongoing disease burden of viruses such as dengue. Structural analysis is key to understand and combat these pathogens. Here, we present a chimeric platform based on an insect-specific flavivirus for the safe and rapid structural analysis of pathogenic viruses. We use this approach to resolve the architecture of two neurotropic viruses and a structure of dengue virus at 2.5  Å, the highest resolution for an enveloped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 77 publications
8
61
0
Order By: Relevance
“…Most of their periphery residues are involved in making contact with adjacent E proteins either to form a dimer (intradimer), interdimer or inter-raft interactions, leaving no gaps on the virus surface. Due to this compactness, mature virus structures have been solved to a higher resolution compared to the immature virus structures—DENV1 (4.5 Å, 4CCT) [ 14 ], DENV2 (3.1 Å, 6ZQU), DENV3 (6 Å, 3J6S) [ 53 ], DENV4 (4.1 Å, 4CBF) [ 51 ], ZIKV (3.7 Å, 5IZ7) [ 54 ], WNV (10 Å, 3J0B [ 55 ]/3.1 Å, 7KVA [ 56 ]) and chimeric DENV2/Binjari virus (2.5 Å, 7KV8 [ 56 ]).…”
Section: The Different Morphological Variants and Their Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of their periphery residues are involved in making contact with adjacent E proteins either to form a dimer (intradimer), interdimer or inter-raft interactions, leaving no gaps on the virus surface. Due to this compactness, mature virus structures have been solved to a higher resolution compared to the immature virus structures—DENV1 (4.5 Å, 4CCT) [ 14 ], DENV2 (3.1 Å, 6ZQU), DENV3 (6 Å, 3J6S) [ 53 ], DENV4 (4.1 Å, 4CBF) [ 51 ], ZIKV (3.7 Å, 5IZ7) [ 54 ], WNV (10 Å, 3J0B [ 55 ]/3.1 Å, 7KVA [ 56 ]) and chimeric DENV2/Binjari virus (2.5 Å, 7KV8 [ 56 ]).…”
Section: The Different Morphological Variants and Their Dynamicsmentioning
confidence: 99%
“…A study on West Nile virus (WNV), another flavivirus, showed that a fusion loop binding antibody, E53, has a time- and temperature-dependent neutralization profile [ 68 ]. This finding suggests that the dynamic nature of E proteins is required for binding, despite its compact appearance of the E proteins on the virus surface under cryoEM [ 56 , 68 ]. Another cross-reactive neutralizing mouse antibody (MAb), 1A1D-2, recognizes an epitope on DIII with 18% of the epitope hidden on the smooth compact DENV2 surface [ 69 ].…”
Section: Virus Morphological Diversity Influences Antibody Bindingmentioning
confidence: 99%
“…Notably, a lipid-binding pocket is also formed by the membrane-associated helices of the envelope glycoproteins E1 and E2 on the surface of mature alphaviruses, with a tryptophan (conserved among mosquito-borne alphaviruses) being involved in the stabilization of this site [45]. [11,12] in mature TBEV (A), Spondweni virus (B), dengue virus serotype 2 (C), and Japanese encephalitis virus (D). Color code: E protein domain I, red; E protein stem, green; transmembrane (TM) domains, gray.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Sequence alignment of stem regions of different flaviviruses using MAFFT (https://www.ebi.ac.uk/Tools/msa/mafft, accessed on 5 July 2021) and ENDscript (http://espript.ibcp.fr/ESPript/ ESPript/, accessed on 5 July 2021) [19]). The yellow star above the sequences labels the conserved tryptophan targeted in this study, the blue dots below the contact residues of E in the pocket site 1 with lipids [12]. TBEV, tick-borne encephalitis virus; OHFV, Omsk hemorrhagic virus; POWV, Powassan virus; KSIV, Karshi virus; DENV1-4, dengue virus serotypes 1-4; ZIKV, Zika virus; SPOV, Spondweni virus; WNV, West Nile virus; JEV, Japanese encephalitis virus; NTAV, Ntaya virus; YFV, yellow fever virus; WSLV, Wesselsbron virus; YOKV, Yokose virus; ENTV, Entebbe bat virus; RBV, Rio Bravo virus; MODV, Modoc virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation